2009
DOI: 10.1163/156856209x404523
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosinase-Catalysed Coating of Wool Fibres With Different Protein-Based Biomaterials

Abstract: The potential of tyrosinases to activate tyrosine residues of wool protein fibres for cross-linking with different materials like collagen, elastin and gelatine was assessed. Natural fibres like wool offer an excellent environment for the growth of micro-organisms when the conditions like moisture, oxygen and temperature are appropriate. Coating with collagen, a very useful biomaterial with bactericidal and fungicidal properties, could be used to improve the properties of wool-based materials, especially when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…In a similar approach, wool fibers have been functionalized with ε-linked polylysine, an FDA-approved biomolecule with antibacterial properties (Wang et al 2010). Recent studies demonstrated that tyrosinase can be employed to oxidize tyrosyl side chains of keratin, allowing crosslinking of proteins such as collagen and elastin to wool fibers (Jus et al 2009; Lantto et al 2012). In the leather industry, transglutaminase-crosslinked preparations of gelatin and casein have been examined as low-cost filling materials to stuff voids in animal hides.…”
Section: Formation Of Protein Networkmentioning
confidence: 99%
“…In a similar approach, wool fibers have been functionalized with ε-linked polylysine, an FDA-approved biomolecule with antibacterial properties (Wang et al 2010). Recent studies demonstrated that tyrosinase can be employed to oxidize tyrosyl side chains of keratin, allowing crosslinking of proteins such as collagen and elastin to wool fibers (Jus et al 2009; Lantto et al 2012). In the leather industry, transglutaminase-crosslinked preparations of gelatin and casein have been examined as low-cost filling materials to stuff voids in animal hides.…”
Section: Formation Of Protein Networkmentioning
confidence: 99%
“…Recently, enzymes are being more fully enlisted for the fabrication and modification of materials [161][162][163][164][165][166][167][168][169][170][171][172][173][174][175][176][177]. Oxidative enzymes especially, tyrosinases, laccases, and peroxidases have been used to generate derivatives of chitosan [178][179][180] and have been extended to generating protein-chitosan conjugates [181].…”
Section: Biofunctionalizing Electrodeposited Chitosan Filmsmentioning
confidence: 99%
“…Due to the ability of tyrosinases to react with phenols, these enzymes have been proposed for the uses in a variety of biotechnological, biosensor and biocatalysis applications [1,8,9]. For example, tyrosinases can be applied in detoxification of phenol-containing wastewater and contaminant soils [10], synthesis of L-3,4-dihydroxyphenylalanine (L-DOPA), one of the preferred drugs for the treatment of Parkinson‘s disease [11], or as additives in food processes due to their cross-linking abilities [12,13].…”
Section: Introductionmentioning
confidence: 99%